Western blotting of native proteins from agarose gels - Chiaki Sakuma; Masataka Nakagawa; Yui Tomioka; Toshiaki Maruyama; Kevin Entzminger; Jonathan K Fleming; Takashi Shibata; Yasunori Kurosawa; CJ Okumura; Tsutomu Arakawa; Teruo Akuta (BioTechniques)
We have developed a new Western blotting method of native proteins from agarose-based gel electrophoresis using a buffer at pH 6.1 containing basic histidine and acidic 2-(N-morpholino)ethanesulfonic acid. This gel electrophoresis successfully provided native structures for a variety of proteins and macromolecular complexes. This paper is focused on the Western blotting of native protein bands separated on agarose gels. Two blotting methods from agarose gel to PVDF membrane are introduced here, one by contact (diffusion) blotting and another by electroblotting after pre-treating the agarose gels with SDS. The contact blotting resulted in the transfer of native GFP, native human plexin domain containing protein 2 (PLXDC2) and native SARS-CoV-2 spike protein, which were detected by conformation-specific antibodies generated in-house.